Epidemiological characteristics and clinical manifestations of pediatric patients with COVID‐19 in China: A multicenter retrospective study. Issue 3 (12th August 2021) - Bai, Yan; Gao, Liwei; Wang, Xianfeng; Zhong, Lili; Li, Jingfeng; Ding, Shenggang; Zheng, Yuejie; Liu, Jun; Cui, Yuxia; Wang, Lina; Han, Mingfeng; Liu, Jun; et al.
ABSTRACT: Importance: The Coronavirus disease 2019 (COVID‐19) global pandemic poses a considerable challenge for pediatricians. Objective: This study aimed to identify the epidemiological characteristics and clinical features of pediatric patients with COVID‐19 in China. Methods: This multicenter retrospective study included pediatric patients from 46 hospitals in China, covering 12 provinces and two municipalities. Epidemiological, demographic, clinical, laboratory, treatment, and outcome data were analyzed. Results: In total, 211 pediatric patients with COVID‐19 were included in this study. The median age was 7.0 years (range: 22 days to 18 years). Approximately 16.3% of the patients exhibited asymptomatic infections, 23.0% had upper respiratory tract infections, and 60.7% had pneumonia, including two with severe pneumonia and one with critical illness. Approximately 78.7% of the pediatric patients occurred in familial clusters. The most three common symptoms or signs at onset in children with COVID‐19 were fever (54.5%), cough (49.3%), and pharyngeal congestion (20.8%). Only 17.6% of the patients presented with decreased lymphocyte count, whereas 13.6% had increased lymphocyte count. Among the patients with pneumonia who exhibited abnormal chest computed tomography findings, 18.2% (23/127) of the patients had no other symptoms. Generally, the chest radiographs showed abnormalities that affected both lungs (49.6%); ground‐glass opacity (47.2%) was the most common manifestation. The cure and improvement rates were 86.7% (183/211) and 13.3% (28/211), respectively. Only one patient with an underlying condition received invasive mechanical ventilation; none of the patients died. Interpretation: Similar to adults, children of all age groups are susceptible to COVID‐19. Fortunately, most pediatric patients have mild symptoms or remain asymptomatic, despite the high incidence of pneumonia. Decreased proportions of white blood cells and lymphocytes are less frequent in children than in adults.